1989
DOI: 10.1007/bf00022610
|View full text |Cite
|
Sign up to set email alerts
|

Variation of the storage protein phaseolin in common bean (Phaseolus vulgaris L.) from the Mediterranean area

Abstract: Variation of phaseolin, the major storage protein in Phaseolus vulgaris L., was analysed in seeds of a germplasm collection from the Mediterranean area . Results showed a number of subvariants differing from the reference patterns for the presence, absence or faintness of single polypeptides . Maximum concentration of variation was found in the Cyprus material . Sources and causes of variation are discussed .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
7

Year Published

1992
1992
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 15 publications
(11 reference statements)
1
14
0
7
Order By: Relevance
“…This occurred as a result of different preferences of farmers in various locations. Lioi, 1989;Chacon et al, 2005). It was reported that 44% of European bean germplasm consists of hybridizations between Andean and Mesoamerican gene pools (Angioi et al, 2010;Santalla et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This occurred as a result of different preferences of farmers in various locations. Lioi, 1989;Chacon et al, 2005). It was reported that 44% of European bean germplasm consists of hybridizations between Andean and Mesoamerican gene pools (Angioi et al, 2010;Santalla et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that globulin, which makes up phaseolin, consists of two major parts: vicilin and legumin. Globulin has been utilized in protein studies since total seed protein consists of 35-50% globulins (Ma and Bliss, 1978;Lioi, 1989;Rodiňo et al, 2001a). However, the exact ratio varies between different bean genotypes (Mcleester et al, 1973).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein marker phaseolin was used as a marker in describing the worldwide dissemination of common bean (Gepts, 1988). A higher frequency of Andean types (T, C, H and A) was recorded with respect to Mesoamerican ones (S, B, M) (Lioi, 1989;Santalla, Rodiño and De Ron, 2002).…”
Section: Evolution Of the Crop Beyond Its Areas Of Origin And Domestimentioning
confidence: 99%
“…These new forms could have subsequently been disseminated to other parts of Europe, contributing to much-wider variation observed in the current European germplasm (Lioi, 1989;Gil and De Ron, 1992;Escribano, De Ron and Amurrio, 1994;Limongelli, Laghetti, Perrino, and Piergiovanni, 1996;Zeven, 1997;González, Monteagudo, Casquero, De Ron and Santalla, 2006). Therefore, the Iberian Peninsula, mainly the north and northwest regions, could be considered as a secondary center of genetic diversity for the common bean crop, especially regarding the large white-seeded cultivars (Santalla et al, 2002;Rodiño et al, 2006).…”
Section: Evolution Of the Crop Beyond Its Areas Of Origin And Domestimentioning
confidence: 99%